2017
DOI: 10.4236/ajps.2017.81002
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Carbon Sequestration to the Physiological and Morphological Traits of Several Green Roof Plants during the First Year after Construction

Abstract: Different vegetation types used for the extensive green roofs have characteristic physiological and morphological traits (e.g., C 3 , C 4 , or CAM photosynthesis, deciduous or evergreen). Several Sedum species are recognized as "inducible CAM" type plants. These differences in the physiological and morphological traits have a considerable effect on the carbon sequestration in the green roofs. The objective of the present study was to quantify the carbon sequestration in several green roof plants during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Acquisition competence of elements (e.g., calcium, carbon, nitrogen) has been quantified by applying growth analysis methods [17][18][19][20][21]. In addition, path analysis has been conducted to quantify the relevance of the relative growth rate (RGR) and its components (e.g., leaf area ratio (LAR), net assimilation rate (NAR), specific leaf area (SLA), and specific nitrogen absorption rate (SAR) in roots) in plant ecology [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition competence of elements (e.g., calcium, carbon, nitrogen) has been quantified by applying growth analysis methods [17][18][19][20][21]. In addition, path analysis has been conducted to quantify the relevance of the relative growth rate (RGR) and its components (e.g., leaf area ratio (LAR), net assimilation rate (NAR), specific leaf area (SLA), and specific nitrogen absorption rate (SAR) in roots) in plant ecology [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Kuronuma and Watanabe (2017b) measured plant and substrate carbon concentrations for Sedum mexicanum on a green roof in Chiba (Japan) for 1 year in a temperate and humid climate. Carbon sequestration amounted to −336 g C m −2 y −1 for wet conditions with regular irrigation and −276 g C m −2 y −1 for periods without irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf area may affect CA by influencing the photosynthesis rate [65]. For instance, an analysis by Kuronoma and Watanabe [66] among three different green roof plants demonstrated that the plant species with the lowest leaf area ratio per whole plant C content had the maximum CS rate. Zoysia matrella (a C4 grass species) had the lowest leaf area ratio per whole plant C content of 0.0094 m 2 (g-C) −1 with a very high CS rate of 2.95 (g-C) pot −1 year −1 or 670 (g-C) m −2 year −1 .…”
Section: Impacts Of Morphological Characteristics On Carbon Accumulat...mentioning
confidence: 99%